1619: Laws enacted by the First General Assembly of Virginia 70, reprinted in H. R. McIlwaine and John P. Kennedy, eds., Journals of the House of Burgesses of Virginia, vol. 1 (Richmond, 1905), 9-14 - (:unkn) unknown (General Publisher, 1619)
Prohibited selling or giving “Indians” arms or ammunition. Punishable by hanging.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES